The Role of Motivation and Teacher Support in Enhancing Elementary Students' Physical Fitness Through Rhythmic Gymnastics Program - Azizah, Maulida Nur; Jusuf, Jeane Betty Kurnia; Santoso, Januar Abdilah; Intani, Andini Dwi; Prayogo, Giri (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study investigates the influence of student motivation and teacher support on predicting physical fitness levels in primary school pupils engaged in rhythmic gymnastics programs. Employing a correlational quantitative methodology, data were gathered from 53 fourth-grade pupils at SD Al-Firdaus Islamic School in Samarinda during April and May 2025. Three validated surveys assessed student motivation (10 items), teacher support (8 items), and physical fitness (7 items) utilizing a 4-point Likert scale. The results indicated substantial positive connections among motivation and physical fitness (r=0.684, p<0.01), teacher support and physical fitness (r=0.496, p<0.01), as well as motivation and teacher support (r=0.642, p<0.01). Multiple regression analysis indicated that motivation and teacher support collectively accounted for 52.3% of the variance in physical fitness (R²=0.523, F=26.914, p<0.001). Motivation was identified as the more significant predictor (β=0.547, p<0.001) in contrast to teacher support (β=0.145, p=0.284). These findings underscore the vital importance of inner and extrinsic motivation in improving physical fitness via rhythmic gymnastics, while instructor support offers significant contextual facilitation.